Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(Q=x^2-y^2-2y-1\)
\(\Rightarrow Q=x^2-\left(y^2+2y+1\right)\)
\(\Rightarrow Q=x^2-\left(y+1\right)^2\)
\(\Rightarrow Q=\left(x-y-1\right)\left(x+y+1\right)\)
Thay \(x=93;y=6\)vào \(Q\)ta được :
\(Q=\left(93-6-1\right)\left(93+6+1\right)\)
\(\Rightarrow Q=86.100\)
\(\Rightarrow Q=8600\)
Vậy \(Q=8600\)
Ta có:x^2-y^2-2y-1
=x^2-(y^2+2y+1)=x^2-(y+1)^2
Thay x=93,y=6 vào bt
93^2-(6+1)^2=8649-49=8600
a) x2−y2−2y−1x2−y2−2y−1 tại x=93x=93 và y=6y=6
Ta có : x2−y2−2y−1=x2−(y2+2y+1)x2−y2−2y−1=x2−(y2+2y+1)
=x2−(y+1)2=x2−(y+1)2
=(x−y−1)(x+y+1)=(x−y−1)(x+y+1)
Khi x=93x=93 và y=6y=6 , ta có :
(93−6−1)(93+6+1)(93−6−1)(93+6+1) =86.100=86.100
=8600
\(x^2-y^2-2y-1\)
\(=x^2-\left(y+1\right)^2\)
\(=\left(x-y-1\right)\left(x+y+1\right)\)
\(=100\cdot\left(93-6-1\right)\)
=8600
Bài giải:
a) x2 + 1212x+ 116116 tại x = 49,75
Ta có: x2 + 1212x+ 116116 = x2 + 2 . x . 1414 + (14)2(14)2= (x+14)2(x+14)2
Với x = 49,75: (49,75+14)2(49,75+14)2= (49,75 + 0,25)2 = 502 = 2500
b) x2 – y2 – 2y – 1 tại x = 93 và y = 6
Ta có: x2 – y2 – 2y – 1 = x2 – (y2 + 2y + 1)
= x2 - (y + 1)2 = (x - y - 1)(x + y + 1)
Với x = 93, y = 6: (93 - 6 - 1)(93 + 6 + 1) = 86 . 100 = 8600
a) \(x^2+\dfrac{1}{2}x+\dfrac{1}{16}\) tại \(x = 49,75\)
Ta có : \(x^2+\dfrac{1}{2}x+\dfrac{1}{16}\) \(=\left(x^2+2.x.\dfrac{1}{4}+\left(\dfrac{1}{4}\right)^2\right)\)
\(=\left(x+\dfrac{1}{4}\right)^2\)
Khi \(x = 49,75\) ,ta có :
\(\left(49,75+\dfrac{1}{4}\right)^2\) \(=\left(\dfrac{200}{4}\right)^2\)
\(= 50^2\)
\(= 2500\)
b) \(x^2 - y^2 - 2y - 1\) tại \(x = 93\) và \(y = 6\)
Ta có : \(x^2 - y^2 - 2y - 1 = x^2 - (y^2 + 2y +1)\)
\(= x^2 - (y + 1)^2\)
\(= (x- y - 1) ( x+ y +1)\)
Khi \(x = 93\) và \(y = 6\) , ta có :
\((93 - 6 - 1) ( 93 + 6 + 1)\) \(= 86 . 100\)
\(= 8600\)